ANALYSIS OF THE EFFECT TOURISM SECTOR AND OPEN UNEMPLOYMENT ON ECONOMIC GROWTH IN BALI PROVINCE - Layla Fickri Amalia; Putu Gita Suari Miranti (Jurnal Statistika Universitas Muhammadiyah Semarang, 2023)
Bali is one of the most popular tourist destinations by domestic and foreign tourists in Indonesia. Because many   tourists visit, many Balinese people are looking for a livelihood in the tourism sector such as being a tour guide, working in the  hospitality sector, culinary, tourist trips etc.  During the COVID-19 pandemic, many workers in the tourism sector lost their jobs, increasing  the open unemployment rate in  Bali Province.  With a high unemployment rate, people's welfare decreases so that it  can affect economic growth in   Bali Province. This study aims to see the Effect of the Tourism Sector and Open Unemployment on Economic  Growth in  Bali Province. The variables of the independent of this study are the number of  tourists visiting, the number of hotel, the  number of travel agencies and the open unemployment rate.  Meanwhile, the dependent variable used is the economic growth of Bali province. The analysis tool used is Panel Data Regression, from the test obtained the value of the coefficient of determination R2 of 65.80%, this shows the magnitude of the influence of independent variables on dependent variables. The results of the study concluded that simultaneously the number of tourists, the number of restaurants, the number of tourist travel agencies, and the unemployment rate influenced economic  growth. This is seen from the prob value of F-statistics of 0.0000. Meanwhile, the results of the t test show that the results are influential and significant for each independent variable against the dependent variable.